Global optimization workshop 2012 - Rocha, Caroline Thennecy de Medeiros (2020)
The Global Optimization Workshop 2012 (GOW 2012) was the eleventh of a series of meetings, organized to be a forum for both academic and industrial communities to present and discuss the latest results and challenges in global optimization